2018
DOI: 10.1080/08869634.2018.1513442
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint disorder determined by Fonseca anamnestic index and associated factors in 18- to 27-year-old university students

Abstract: In the prevention and treatment of TMD, a holistic approach that evaluates mechanical factors and psychosocial factors should be adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
4
14
0
Order By: Relevance
“…5,11,12,16,31 Subclinical symptoms of TMD have been investigated with FAI, which is used in the early diagnosis and detection of TMD to prevent the progression and early treatment of TMD symptoms, enabling the rapid and accessible collection of large amounts of data at the minimum cost used in many previous studies. 5,19,32,33 Similar to previous studies conducted in various university student populations and reported TMD prevalence between 37-80% 5,[13][14][15][16][17]19,25 , this study, which included only dental assistant program students, also found a high prevalence of TMD (64.8%) compared to the prevalence of TMD absence (35.2%). These results may be due to differences in populations such as genetic structure, physiological differences, sex distribution, or social demographic characteristics, and the anxiety caused by the COVID-19 pandemic at the time of the study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…5,11,12,16,31 Subclinical symptoms of TMD have been investigated with FAI, which is used in the early diagnosis and detection of TMD to prevent the progression and early treatment of TMD symptoms, enabling the rapid and accessible collection of large amounts of data at the minimum cost used in many previous studies. 5,19,32,33 Similar to previous studies conducted in various university student populations and reported TMD prevalence between 37-80% 5,[13][14][15][16][17]19,25 , this study, which included only dental assistant program students, also found a high prevalence of TMD (64.8%) compared to the prevalence of TMD absence (35.2%). These results may be due to differences in populations such as genetic structure, physiological differences, sex distribution, or social demographic characteristics, and the anxiety caused by the COVID-19 pandemic at the time of the study.…”
Section: Discussionsupporting
confidence: 86%
“…[11][12][13] Most of the epidemiological studies conducted on determining the prevalence of TMD have been conducted on university students studying any field related to health services. 1,3,5,[14][15][16][17] It has been reported that the prevalence of TMD shows a wide range between 47-81% in studies conducted on students from the Turkish population, with studies conducted in some of the populations. [15][16][17][18][19] TMD problems have been reported to be on the rise in the adolescent and adult population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability in prevalence may be due to factors such as the variability of the number of samples used in the studies and the period in which the study was conducted. Özdinç et al [35] examined the relationship between stress level, sleep quality, and TMD in university students; the study results reported that the prevalence of TMD among university students was 60.50%, and TMD was observed more in females than males. Similiar to the previous study, Çebi [36] reported that the majority of TMD appeared in young and adult females more often than males.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the present study, the frequency of TMD in females was found to be higher than in males, which was supported by a previous study. Also, Özdinç et al [35] demonstrated that PSQI scores and perceived stress scores were increased in individuals with TMD and argued that sleep quality and perceived stress are important risk factors for TMD. Unlike the previous study results, the current study evaluated the TMD frequency, sleep quality, and DASS-21 score during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%